The contribution of the Chaamba to popular uprisings in Southern Algeria during the nineteenth century - DINE, Souria; SAMMARI, Boubaker (The International tax journal, 2025)
This research aims to highlight the significant role played by the Chaamba tribes in the popular uprisings of southern Algeria during the nineteenth century, examining their military and social contributions in resisting French expansion. The findings show that the Chaamba were a decisive force supporting most resistance movements, whether led by Sharif Muhammad ibn Abdallah, Bouchoucha, the Ouled Sidi Sheikh, or Sheikh Bouamama. The study also reveals that their support extended beyond combat to include supplying resources, providing refuge, and organizing operations, making them the first line of defense for the Sahara. The results indicate that their steadfastness delayed French penetration into the deep south for nearly half a century. The study concludes that the Chaamba’s role was central to shaping the region’s resistance memory and merits further research and documentation.